Algorithmic Dissemination of Javanese Cultural Narrative Heritage: A Semiotic Study of TikTok's Cyberspace of the Museum Karaton Surakarta Hadiningrat for Enterprise Development - Maram Taher; Dwi Susanto; Sri Kusumo Habsari (Javanologi: International Journal of Javanese Studies, 2026)
This paper examines the semiotics of symbols and meanings in promoting Javanese cultural heritage and the historic architecture of the Museum Karaton Surakarta Hadiningrat through TikTok. While prior research has explored heritage communication in cyberspaces, few studies have investigated how algorithmic dynamics on short-form video platforms shape cultural visibility. Employing a mixed-methods design combining content analysis, digital ethnography, and algorithm engagement tracking this study applies a semiotic analytical model to evaluate cultural representation strategies. Findings demonstrate that heritage-focused videos achieve greater reach and audience retention when aligned with trending formats, participatory storytelling, and platform-specific concordances. Theoretically, this research introduces a model of algorithmic cultural dissemination; practically, it offers strategies for heritage institutions to strengthen cultural business, smart enterprise development. Ultimately, the study underscores the potential of media algorithms not only as entertainment mechanisms but also as powerful tools of narrative storytelling, museum management innovation, and the advancement of sustainable cultural practices with both national and global impact.